Landscape Management Facilitation of BUMDes Arih Ersada's Taman Seribu Bunga to Increase Agrotourism Attraction in Raya Village, Karo Regency (Talenta Publisher Universitas Sumatera Utara, 2024)
The target of rural development is village independence and prosperity, that can be achieved by managing village economic institutions, BUMDes (village-owned enterprises). BUMDes is a business entity where the village directly or mostly owns its capital through direct participation, derived from the village’s separated assets, to manage assets, provide services, and engage in other businesses for the welfare of the village community. When BUMDes is able to operate well, generate profits that contribute more to the village's income (PADes) and reduce its unemployment, then the village will be more independent and prosperous. North Sumatra Province has 5,417 village areas but based on the Developing Village Index (IDM), there are only 16 villages with independent status. This indicates that the rural development in North Sumatra still needs to be carried out continuously. In Karo Regency, there is an independent succeed village because it is able to utilize the potential of existing natural resources, namely Raya Village, Berastagi District. This village owns a BUMDes called Arih Ersada that manages the Taman Seribu Bunga Agrotourism business unit, which always needs to be maintained and improved, so that it continuously contributes optimally to the development and empowerment of the community in Raya Village. This service activity is trying to do something that will improve the quality and functionality of Taman Seribu Bunga Agrotourism through landscape management in order to increase visitors as an effort to increase BUMDES income and empower the Raya village community.